Curve-fitting and econometric oil production models in Brazil - Hallack, Larissa Nogueira (2019)
This work develops multi-Hubbert and asymmetrical oil production cycles to analyze the Brazilian post-salt oil production offshore. A hybrid model employs regression analysis to explain the deviation of crude oil production rate from the Hubbert curve. By looking at the creaming phenomenon, this thesis evaluates the potential for future oil discoveries in Brazil. A creaming curve variant employs the fields’ size of discoveries based on the assumption that the recovery factor is the same for all fields within a sedimentary basin. This assumption is necessary because the size of the fields’ reserves is confidential data. In addition, this thesis analyzes the number of development wells completed in the pre-salt zones by using time series econometric techniques of cointegration and error correction modeling. Following an increase in the country risk, and the 2014 oil price collapse, this thesis analyzes the number of development wells drilled in the pre-salt zones by identifying the effect of oil price, price volatility, productivity, and country risk. Results show the negative and positive effect of raising, respectively, the country risk and productivity for the number of pre-salt development wells.